Artemisia flaccida (Asteraceae, Anthemideae) is merged with A. fulgens, with transfer of A. flaccida var. meiguensis to A. fulgens - Guo, Xin-Qiang; Wang, Long; Yang, Qin-Er (Phytotaxa, 2021)
Based on observations on herbarium specimens (including type material) and living plants in the wild, we demonstrate that Artemisia flaccida (Asteraceae, Anthemideae) is conspecific with A. fulgens and that A. flaccida var. meiguensis deserves a varietal status under A. fulgens. We therefore place A. flaccida in synonymy with A. fulgens and transfer A. flaccida var. meiguensis to A. fulgens as A. fulgens var. meiguensis. Lectotypification is proposed for A. fulgens and A. flaccida. The geographical distribution of the two varieties of A. fulgens, var. fulgens and var. meiguensis, is also clarified.